Web assisted language learning system for enhancing Arabic language learning using cognates - Shehab, Roaya; Zeki, Akram M. (Universiti Teknologi Malaysia, 2015)
This paper aims to study the use of the WWW in the learning and teaching of Arabic as a second language. Moreover, it aims to study the combination of Web Assisted Language Learning (WALL) and cognate (words similar in meaning and pronunciation) transfer for Arabic language. In addition, the main goal of this paper is to enhance learning of the Arabic language with the approach of WALL. Therefore, the authors built an Arabic WALL system that automatically identifies cognates in Arabic and any other language. The WALL system displays the cognates in a list and as lessons. However, for evaluating the system, Malay language was chosen to be stored in the database. To evaluate the system, a quantitative method was used in the study. A survey was conducted among two groups of respondents. The respondents of the first group were five (5) Malay-speaking learners. The respondents of the second group were five (5) teachers who teach Arabic to Malaysian students. The questionnaire consisted of 14 closed questions (five-point Likert scale). It was found that the majority of participants were satisfied using the system and that they preferred it over traditional learning. They also found the system to be an effective learning tool. Overall, the findings showed that the goals of the study had been achieved.